Antioxidant and hepatoprotective effects of Hypsizygus ulmarius polysaccharide on alcoholic liver injury in rats - Sudha Govindan; Angu Jayabal; Jayasakthi Shanmugam; Prasanna Ramani (Food Science and Human Wellness)
Hypsizygus ulmarius polysaccharide (HUP) is a water-soluble polysaccharide obtained by hot water extraction, followed by precipitation and deproteinization. The characteristics of HUP, antioxidant activity and liver protection against alcohol-induced liver damage were studied. Structural characteristics indicate that the HUP is a pyran-type polysaccharide with a molecular weight of 2076 Da. In antioxidant scavenging assay, HUP showed moderate DMPD radical scavenging activity, cupric ion reducing antioxidant capacity and inhibitory effect against lipid peroxidation in a dose-dependent manner. Regarding in vivo hepatoprotective activity, compared with the ethanol induction group, pre-treatment of low and high doses of HUP significantly reduced the behaviours of serum enzymes, lowered the levels of hepatic oxidative stress markers, restored the levels of biochemical constituents, enhanced the levels of liver and serum enzymatic antioxidants and non-enzymatic antioxidants, and improved the serum lipid levels of alcohol-intoxicated rats. The hepatoprotective effect of HUP was comparable to positive control silymarin. Besides, HUP pre-treatment significantly normalized the histopathological changes induced by ethanol. The results indicate that HUP could be used as a functional food and may protect the biological system from oxidative stress through its antioxidant activity, thus having a significant protective effect on acute alcoholic liver injury.